The primary pathway for lactate oxidation in Desulfovibrio vulgaris - Vita, Nicolas; Valette, Odile; Brasseur, Gaël; Lignon, Sabrina; Denis, Yann; Ansaldi, Mireille; Dolla, Alain; Pieulle, Laetitia (Frontiers in Microbiology, 2015)
The ability to respire sulfate linked to lactate oxidation is a key metabolic signature of the Desulfovibrio genus. Lactate oxidation by these incomplete oxidizers generates reductants through lactate dehydrogenase (LDH) and pyruvate-ferredoxin oxidoreductase (PFOR), with the latter catalyzing pyruvate conversion into acetyl-CoA. Acetyl-CoA is the source of substrate-level phosphorylation though the production of ATP. Here, we show that these crucial steps are performed by enzymes encoded by a nonacistronic transcriptional unit named now as operon luo (for lactate utilization operon). Using a combination of genetic and biochemical techniques, we assigned a physiological role to the operon genes DVU3027-28 and DVU3032-33. The growth of mutant 26-28 was highly disrupted on D-lactate, whereas the growth of mutant 32-33 was slower on L-lactate, which could be related to a decrease in the activity of D-lactate or L-lactate oxidase in the corresponding mutants. The DVU3027-28 and DVU3032-33 genes thus encode functional D-LDH and L-LDH enzymes, respectively. Scanning of the genome for lactate utilization revealed several lactate permease and dehydrogenase homologs. However, transcriptional compensation was not observed in any of the mutants except for lactate permease. Although there is a high degree of redundancy for lactate oxidase, it is not functionally efficient in LDH mutants. This result could be related to the identification of several operon enzymes, including LDHs, in the PFOR activity bands, suggesting the occurrence of a lactate-oxidizing supermolecular structure that can optimize the performance of lactate utilization in Desulfovibrio species.